2010
DOI: 10.1097/ico.0b013e3181bd4bc1
|View full text |Cite
|
Sign up to set email alerts
|

Multipurpose Solutions and Contact Lens: Modulation of Cytotoxicity and Apoptosis on the Ocular Surface

Abstract: MPS can be damaging for the ocular surface cells. We proposed to rinse the lens with a marine solution before insertion of the lens on the cornea to wash away the multipurpose solution and to use hyaluronic acid to protect the ocular surface cells against apoptosis induced by MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 14 publications
1
20
0
2
Order By: Relevance
“…As it induced cell death as soon as 30 minutes, we also evaluated the benefits of a rinse step after use of this solution and observed that unpreserved saline solutions again avoided cytotoxicity. In each case, the controlled ionization controlled marine solution was more efficient than NaCl 0.9% to rinse contact lenses, which is in accordance with previous results (Dutot et al, 2010;Said et al, 2009). Oligoelements and ions are already known to exert beneficial ocular effects (Dutot et al, 2008b).…”
Section: Efficacy Of a Contact Lens Rinse Step With Unpreserved Solutsupporting
confidence: 81%
See 1 more Smart Citation
“…As it induced cell death as soon as 30 minutes, we also evaluated the benefits of a rinse step after use of this solution and observed that unpreserved saline solutions again avoided cytotoxicity. In each case, the controlled ionization controlled marine solution was more efficient than NaCl 0.9% to rinse contact lenses, which is in accordance with previous results (Dutot et al, 2010;Said et al, 2009). Oligoelements and ions are already known to exert beneficial ocular effects (Dutot et al, 2008b).…”
Section: Efficacy Of a Contact Lens Rinse Step With Unpreserved Solutsupporting
confidence: 81%
“…the plate was agitated on a microplate shaker for 30 min. The neutral red fluorescence was then measured (λex 535 nm; λem 600 nm) in accordance with our validated protocol (Dutot et al, 2010;Rat et al, 1994).…”
Section: Experimental Procedures To Adapt Iso 10993-5 Standardmentioning
confidence: 99%
“…Such prolonged contact period could make the anterior corneal stroma more vulnerable to the effects of MPS shown in this study. Previous studies (HorwathWinter et al, 2004;Wright and Mowrey-McKee, 2005;Chuang et al, 2008;McCanna et al, 2008;Cavet et al, 2009Cavet et al, , 2010Dutot et al, 2010) investigated the effects of MPS on corneal epithelial biocompatibility using epithelial cell viability assay, expression measurement, distribution of tight junction protein and electrical resistance across the epithelial cells. To the best of our knowledge, this is the first study to assess the effects of MPS on the anterior corneal stromal collagen.…”
Section: Discussionmentioning
confidence: 99%
“…They are composed mainly of antimicrobial and buffering agents and in most cases, surfactants. In vitro cytotoxicity studies provide evidence of the toxicity of MPS ingredients on the corneal epithelium (Dutot et al, 2008(Dutot et al, , 2010Tanti et al, 2011;Gorbet et al, 2011) linking it to the high drop-out rate of contact lens wearers (Schlitzer, 1992). The commercially available MPS differ in their concentration and chemical compositions and could have differential effects on the cornea with respect to its function and structural integrity (Lievens et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…12,13 Recently, there has been increasing debate regarding the relevance of SICS and what it represents 6,14-17 and whether it is a sign of a true and relevant corneal response to CL/LCS bioincompatibility or a nonsignificant sign merely induced by exposure to certain CL/LCS combinations. While several in vitro studies [18][19][20][21][22] support the hypothesis that solutions may cause varying degrees of cytotoxicity, most in vitro models are too simplistic to allow for clinical correlations of lens/LCS biocompatibility and thus a clinical evaluation is necessary to shed some light on the relevant importance of the SICS response.…”
Section: Introductionmentioning
confidence: 99%